Asset Management Based on Risk Control and Information Systems - Yudha Adi Kusuma; Aan Zainal Muttaqin (TALENTA Publisher, 2022)
Asset management is needed in asset inventory. The preparation of an asset inventory is taken into account the aspects of asset management and risk management. The measurement results with SEM obtained APC values and values < 0.05 and AVIF < 5 so that the relationship between the criteria for asset management and risk management has a significant effect on the design of asset information systems. Measurement of risk management obtained 4 critical risks that affect the design of asset information systems. One of the asset information systems that meet the criteria of being integrated, easy to manage, and easy to update the data is a QR code-based check sheet. Its use in a small scope is easier to implement than using a database system.